Assessment for Learning and Value Internalization: Cognitive Assessment in Islamic Religious Education at Indonesian Middle Schools - Lailatus Sa'adah; Agus Fakhruddin; Saepul Anwar (Bulletin of Indonesian Islamic Studies, 2025)
Assessment in Islamic Religious Education (PAI) plays a strategic role in measuring cognitive achievement while simultaneously internalizing religious values. This aligns with the theory of assessment for learning, which emphasizes assessment as a continuous process of constructive feedback and Bloom’s taxonomy as a reference for developing cognitive questions from lower to higher-order thinking. This study analyzes the cognitive assessment practices of PAI teachers at a junior high school in Bandung, covering teachers’ understanding, planning, implementation, use of assessment results, and professional development. A qualitative approach with an instrumental case study design was employed, involving four purposively selected PAI teachers. Data were collected through structured interviews, classroom observations, and document analysis of teaching modules, test items, and rubrics, then analyzed using Huberman’s stages of reduction, presentation, and conclusion drawing. Findings reveal that assessment planning is supported by curriculum and MGMP forums, though rubrics remain holistic; implementation combines various techniques but written tests dominate; results are used for remedial; while professional development occurs through MGMP but still requires practical training on HOTS and analytic rubrics. This study contributes by mapping the contextual assessment cycle of PAI and recommending rubric strengthening, differentiation, and continuous professional development, enabling assessment to function as both a driver of holistic learning and a medium for value internalization.